DESIGN THINKING COMO ESTRATEGIA PEDAGÓGICA EN LA FORMACIÓN DE UN APRENDIZAJE SIGNIFICATIVO EN ESTUDIANTES DE 4TO GRADO EGB DE LA ESCUELA UNIDOS APRENDEREMOS PERIODO 2024-2025. - VILLA MORA LITZI MAYERLI (2024)
The purpose of this case study is to determine Design Thinking as a pedagogical strategy in the formation of meaningful learning. To do so, objectives were set focused on analyzing the influence of the design thinking strategy. Nowadays, in education, the search for meaningful knowledge is encouraged, where students have the opportunity to express their opinion, explore their knowledge and be autonomous, allowing them to develop their self-esteem and self-control. These particularities of this educational methodology allow for the establishment of good interpersonal relationships; it is important to highlight that the lack of application of active didactic strategies is one of the sources of demotivation of students, since it is a limitation in the growth of their innovation and creativity.